Non-singular coordinates of some black hole in f(R) gravity - Riaz, S. M. J.; Hussain, R. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Non-singular Kruskal-like coordinates of some black holes space-times in f (R) gravity are presented in this research paper, and are also removed by establishing Kruskal-Szekeres coordinates for Non-extremal case. Carter-like coordinates can also be built for its extreme case. В статье представлены несингулярные координаты типа Крускала пространства-времени некоторых черных дыр в гравитации f (R). Сингулярности координат могут быть удалены путем установления координат Крускала-Секереша для неэкстремального случая. Для экстремального случая могут быть построены координаты типа Картера.
Keywords: Gravitation